Effect of Prenatal Yoga on Sodium and Potassium Levels Among Madurese Women with Pre-eclampsia: A Quasi-Experimental Study - Eny Susanti; Zakkiyatus Zainiyah; Novita Wulandari; Sriyana Herman; Mochamad Amin; Iswahyudi Iswahyudi (Public Health of Indonesia, 2026)
Background: Preeclampsia is a hypertensive disorder of pregnancy (HDP), characterised by trophoblast immaturity and vascular dysfunction. Preeclampsia is characterised by blood pressure >140/90 mmHg and proteinuria. Preeclampsia can be prevented by maintaining a healthy diet and engaging in regular exercise during pregnancy, including yoga.  Objectives: To analyse the effect of Prenatal Yoga on Sodium and Potassium Levels Among Madurese Women with Pre-eclampsia. Methods: This study employed a quasi-experimental design involving 14 pregnant women diagnosed with preeclampsia and an equivalent number of 14 pregnant women in good health. Prenatal yoga sessions were conducted weekly for 8 weeks. Expectant mothers were selected according to specific inclusion and exclusion criteria. Serum specimens were collected using Elabscience assay kits. Serum sodium and potassium concentrations were analysed before and after prenatal yoga. The data were tested for normality, and the Wilcoxon test was used. Results: This study showed a significant difference in serum potassium levels before a mean of 3.29 and after a mean of 4.23 prenatal yoga in preeclamptic pregnant women (p=0.016), although there was no significant difference in serum sodium levels (p>0.05) before a mean of 150.15 and after a mean of 126.11 prenatal yoga in preeclamptic pregnant women. Conclusion: Helping to prevent hypertension during pregnancy. Prenatal yoga may reduce the risk of pre-eclampsia and improve maternal and fetal morbidity and mortality.